Feasibility of FDM-electroplating process for EDM electrode fabrication. (2020) - Sood, Anoop Kumar; Equbal, Azhar
Abstract: The present research proposes the applicability of fused deposition modelling (FDM) based additive manufacturing (AM) process to fabricate the electric discharge machining (EDM) electrodes. The entire research is divided into three stages. In the first stage, FDM fabricated part properties were improved in terms of its dimensional accuracy, mechanical strength and surface finish. In the second stage, conductivity properties were induced in a material and copper is deposited over the part through electroplating to generate the electrode suitable for EDM machining. In the final stage, fabricated electrodes were used for machining. Material removal rate ( MRR ), tool wear rate ( TWR ), average surface roughness ( R a ) of machined surface and dimensional deviation ( DA ) in terms of diameter and the depth of the machined hole are used for assessing the machining performance. The obtained results were compared with machining using a conventional electrode under similar machining conditions. Central composite design supported by the statistical techniques namely analysis of variance (ANOVA) and two sample t-tests were used for conducting experiments and analysis of results. It is proposed that the performance of the conventional electrode and the electrode fabricated through FDM-electroplating process are same in terms of MRR, TWR, and R a . However, FDM-electroplated electrodes are more suitable where the tolerance interval is broader in comparison to the conventional electrode.